The uniformization process of the fast congestion notification (FN) - M. Kadhum, Mohammed; Hassan, Suhaidi (LJS Publisher and IJCSIS Press, 2009)
Fast Congestion Notification (FN) is one of the proactive queue management mechanisms that practices congestion avoidance to help avoid the beginning of congestion by marking/dropping packets before the router’s queue gets full; and exercises congestion control, when congestion avoidance fails, by increasing the rate of packet marking/dropping. Technically, FN avoids the queue overflows by controlling the instantaneous queue size below the optimal queue size, and control congestion by keeping the average arrival rate close to the outgoing link capacity. Upon arrival of each packet, FN uses the instantaneous queue size and the average arrival rate to calculate the packet marking/dropping probability. FN marks/drops packets at fairly regular intervals to avoid long intermarking intervals and clustered packet marks/drops. Too many marked/dropped packets close together can cause global synchronization, and also too long packet intermarking times between marked/dropped packets can cause large queue sizes and congestion. This paper shows how FN controls the queue size, avoids congestion, and reduces global synchronization by uniformizing marked/dropped packet intervals.